Ontology on the level g of the software process model MPS.Br to assist business processes modeling - Pizzoleto, Alessandro Viola [UNESP]; De Oliveira, Hilda Carvalho [UNESP]; Oliveira, Celso Socorro [UNESP] (My University, 2012)
This paper presents a new way to organize the software process quality model MPS.Br through the definition of an ontology implemented in OWL. Considering the seven levels of maturity the MPS.Br, this work shows how the ontology was developed for the lower level, G. Financial and nonfinancial indicators of the model BSC (Balanced Scorecard) were integrated into the model MPS.Br to facilitate alignment with the company's strategic planning and business model. The goal is to contribute to the mapping of the processes and other information from the MPS.Br for a generic model of BPM (Business Process Management). This generic model can be used by micro and small enterprises to organize their software production line and then achieve MPS.BR certification.
Keywords: BPM; BSC; Enterprise ontology; MPS.Br; Ontology; OWL; Software quality